A moderated mediation model in assessing links between rumination, emotional reactivity, and suicidal risk in alcohol use disorder - Mateusz Wojtczak; Karol Karasiewicz; Katarzyna Kucharska (Frontiers in Psychiatry)
IntroductionSuicide is a major public health concern, particularly among people with alcohol use disorders (AUD). Rumination, as a dysfunctional emotion regulation strategy, and increased emotional reactivity may significantly influence suicide risk in this population.AimThe aim of this study was to assess whether different emotional reactivity mediate the association between ruminations and suicide risk, and whether AUD or control group (HC) status moderates these relationships.MethodsA study was conducted with 152 participants, including 86 from AUD and 66 from HC. Self-report questionnaires measuring ruminations, emotional reactivity and suicide risk were used. Structural Equation Modeling, invariance analysis, and moderated mediation estimation were used in the analyses.ResultsThe mediation analysis in the full sample revealed a significant indirect effect of rumination on suicide risk via emotional reactivity. Multi-group analysis indicated no significant differences in the mediation effect between the AUD and HC groups, with neither group showing a statistically significant indirect effect.ConclusionsThe findings indicate that emotional reactivity may serve as a key mechanism mediating the relationship between rumination and suicide risk. Therapeutic interventions should focus on reducing ruminations and emotion reactivity to effectively reduce suicide risk in this group. Further research is needed to better understand these mechanisms.